UDDER THERMOGRAPHY OF GYR COWS FOR SUBCLINICAL MASTITIS DETECTION / TERMOGRAFIA DO ÚBERE DE VACAS GIR PARA DETECÇÃO DE MASTITE SUBCLÍNICA - PORCIONATO, MARCO AURÉLIO F.; CANATA, TATIANA F.; OLIVEIRA, CELSO E. L. DE; SANTOS, MARCOS V. DOS (Revista Brasileira de Engenharia de Biossistemas, 2009)
Aiming to evaluate the infrared thermography technique for early detection of subclinical mastitis in Gyr cows, 70 animals were selected in 2nd or 3rd lactation, with an average production of 7.2 kg / d between 90 and 200 days in milking. Images of two quarters (front and backside) of the same udder side were monthly performed during three months using a thermal camera to evaluate the surface temperature at three different heights (upper, median and lower), totalizing 420 measurements. Milk samples from each quarter were also collected to evaluate the SCC and microbiological culture. The SCC did not influence udder temperature at different heights (p>0.05). However, temperatures among the regions of the quarter were different, the upper area had higher values than the median and lower regions (p<0.05). There was no difference in udder temperatures in relation to the type of microorganisms isolated in milk (p>0.05). The use of thermal camera allowed the identification of temperature variations of skin surface at different udder regions of Gyr cows. However, this technique was not effective in the detection of subclinical mastitis.